Exploring the potential of Salicornia: A halophyte’s impact on Agriculture, the Environment, and the Economy - Katel, Shambhu (2023)
Salicornia, a halophytic plant, garners attention for its environmental, energy, medicinal, and economic potential. It excels in environmental management through phytoremediation and carbon sequestration, thriving in saline environments to filter toxins and recycle nutrients. As a biofuel source, its oil-rich seeds and high biomass yield offer eco-friendly alternatives for biodiesel and bioethanol production, mitigating greenhouse gas emissions. Salicornia’s bioactive compounds exhibit significant potential in modulating the immune system and managing various diseases. Despite challenges such as production costs and regulatory barriers, Salicornia holds promise as a sustainable crop with diverse commercial applications. Scaling up Salicornia production and utilization requires addressing challenges related to cultivar development, production costs, and regulatory frameworks. However, with continued research and investment, Salicornia could emerge as a valuable resource for addressing food security, energy sustainability, and environmental restoration. Future research directions include exploring Salicornia’s nutritional composition, environmental sustainability, and epigenetic mechanisms, as well as optimizing extraction methods and intercropping systems. Understanding these aspects will contribute to unlocking Salicornia’s full potential as a versatile crop with wide-ranging benefits for human health, environmental conservation, and economic development.